Wastewater Treatment Concepts and Practices. - Hopcroft, Francis (Momentum Press, 2014)
This book provides a concise presentation of the fundamental elements of wastewater treatment process design. It shows the reader where various authors and authorities differ in their interpretation of the fundamentals and offers multiple tables of data from which to select appropriate design parameters. This book is intended to be a process design reference book, not a detailed design manual or a textbook suitable for classroom use.